Transcatheter versus surgical aortic valve replacement in low to intermediate risk patients: A meta-analysis of randomized and observational studies. (1st February 2017) - Zhou, Yijiang; Wang, Yanwei; Wu, Yutao; Zhu, Jianhua
Abstract: Background: Transcatheter aortic valve replacement( TAVR) has become the treatment of choice for patients with aortic stenosis and the preferred alternative for high surgical risk patients. However, TAVR's suitability for patients at low to intermediate risk still remains controversial. Methods: PubMed, MEDLINE and Clinical trials were systematically searched for randomized control trials and observational cohort studies which reported the clinical outcomes of TAVR versus surgical aortic valve replacement( SAVR) in patients at low to intermediate surgical risk. Clinical endpoints including death, acute kidney injury, myocardial infarction, and major adverse cardiac and cerebrovascular events (MACCE) were assessed. Results: From 2000 to 2016, 7 clinical studies comprising 6214 patients were identified. In each time point (in-hospital or 30 days, 1 year), TAVR was associated with similar incidence of death from any cause, cardiovascular death and MACCE. TAVR reduced short-term incidence of myocardial infarction and cerebrovascular events. However, TAVR was associated with a higher rate of major vascular complications and permanent pacemaker implantation. Conclusions: Comparing with SAVR in patients at low to intermediate surgical risk, TAVR has similar rates of mortality and MACCE, lower incidence of acute kidney injury and new-onset atrial fibrillation, but an increase in major vascular complications and permanent pacemaker implantation.